Triple-Negative Lobular Breast Cancer Causing Hydronephrosis - Michael Chahin DO; Hardik Chhatrala MD; Nithya Krishnan MD; Darren Brow MD; Lara Zuberi MD (SAGE Publishing, 2020)
Breast cancer is the leading malignancy and the second most common cause of mortality in women. Although there have been advances in identifying biomarkers as potential targets for therapy, triple-negative breast cancer (TNBC) continues to have a poorer prognosis than the other receptor subtypes. The most common sites of metastasis are bone, liver, lung, and brain. We present a patient with known TNBC presenting with nausea and vomiting in whom computed tomography revealed a right-side pelvic mass causing hydronephrosis. Biopsy was consistent with TNBC of the ureter, an unusual site for breast cancer involvement. She required ureteral stent placement to relieve obstruction and has had good response to paclitaxel. Hydronephrosis due to malignancy presents significant risk of morbidity and mortality due to compromised renal function and must be resolved promptly to avoid compromise of renal function.